Pengaruh Kualitas Pelayanan dan Kepercayaan Merek Terhadap Proses Keputusan Pembelian Asuransi Jiwa Di PT BNILife Insurancae (studi kasus pada nasabah Bank BNI KK Grand Wisata) - Sisilia Manorek, Ike; Maulina, Anita; Arizona Bandi, Anisa (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This Research Aims To Know The Influence Of Service Quality And Brand Trust On The Life Insurance Purchase Decision Process At Pt Bnilife Insurance (Case Study on Customers of Bank Bni Kk Grand Wisata), The research method used is quantitative method. Data collection techniques used in the form of questionnaires and literature. The population in this research is BNI KK Grand Wisata Bekasi customers who buy BNILIFE life insurance products. Sampling used by using random samples or random samples, taking the sample the researcher "mixed" the subjects in the population so that all subjects are considered the same. The sample consists of 46 samples. Analysis of the data used is multiple linear regression analysis using the help of IBM Statistics software version 26. The results showed that the quality of service with a percentage level of influence of 31.9%. Brand trust with a percentage level of influence of 37.2%. purchase with a significance value of 37.2%. Quality of service and brand trust in the Life Insurance Purchase Decision Process at PT BNILIFE Insurance (a case study on customers of Bank BNI KK Grand Wisata) with a percentage level of influence of 43.3%.